CRIMINAL PSYCHOLOGY IN SPAIN: PRESENT AND FUTURE - José Luis González (Papeles del Psicólogo, 2015)
As part of legal psychology, as it is understood in Spain, we can distinguish between the applications of psychology in the different steps of the judicial process: in police stations during criminal investigations, in court when the perpetrators have already been identified and arrested, and in prisons where they are eventually sent after being convicted. This paper argues that when psychology assists the criminal investigation in the first step of the judicial process - the police activities-, we are talking about criminal psychology, at two levels: the operational level (mostly pertaining to criminal psychology) and the strategic level (shared with other areas of expertise). After describing its peculiarities and specific areas, in analogy with the support provided by other forensic sciences, we explain that in Spain this specialty is carried out professionally from within our own police forces, with a profile that is very different from the more traditional police psychology, and in close collaboration with the academic environment with regard to the scientific development of techniques and procedures.